Lithium-doped calcium silicate scaffolds induce miR-130a-rich M2 macrophage EV-accelerating diabetic bone healing through angiogenesis–osteogenic coupling and mitochondrial repair - Ting-You Kuo; Cheng-Yu Chen; Yen-Hong Lin; Der-Yang Cho; Tsung-Li Lin; Ming-You Shie (Chemical Engineering Journal, 2026)

High-throughput pesticide toxicity assessment in Black Soldier Fly (Hermetia illucens) by behavioral phenomics - Petrus Siregar; Gilbert Audira; Kevin Adi Kurnia; Szu-Chieh Wang; Marri Jmelou M. Roldan; Kristine Mae.H. Bonalos; Ross D. Vasquez; Ming-Der Lin; Chung-Der Hsiao (Pesticide Biochemistry and Physiology, 2026)

Unveiling the multifaceted efficacy of Gu Sui Bu in osteoporosis treatment: insights from a zebrafish model and advanced analytical approaches - Wen-Ying Lin; Cheng-Huan Peng; Ming-Der Lin (Phytochemistry Letters, 2025)

Dual-functional tight ultrafiltration membrane constructed from aminoquinone networks for sufficient dye/salt selectivity and bacterial inactivation - Riri Liu; Hanna Vanermen; Jiale Du; Qin Chen; Zijian Yu; Junwei Li; Pengrui Jin; Junfeng Zheng; Alexander Volodin; Wenyuan Ye; Raf Dewil; Ming Xie; et al. (Desalination, 2025)

Tight ultrafiltration membranes based on engineered metal-monophenolic networks for efficient dye/NaCl separation - Riri Liu; Qin Chen; Jiale Du; Yanyan Liu; Alexander Volodin; Patricia Luis; Wenyuan Ye; Raf Dewil; Ming Xie; Jiuyang Lin; Bart Van der Bruggen (Desalination, 2025)

Genetic Analysis of Polyunsaturated Fatty Acids Biosynthesis Pathway Determines Four Distinct Thraustochytrid Types - Sou‐Yu Cheng; Yi‐Jing Chen; Hsiu‐Chin Lin; Hsin‐Yang Chang; Ming‐Der Huang (Environmental Microbiology, 2025)
Thraustochytrids, diverse marine unicellular protists encompassing over 10 recognised genera, are renowned for synthesising polyunsaturated fatty acids (PUFAs), with content and composition varying substantially across genera. While PUFAs are known to be produced via PUFA synthase (PUFA‐S) and/or elongase/desaturase (ELO/DES) pathways, the distinctions in genes involved remain unexplored. This study analysed PUFA biosynthetic genes in 19 thraustochytrid strains across six genera, categorising them into four types. Type I exclusively utilises the ELO/DES pathway, Type II employs both PUFA‐S and complete ELO/DES pathways, while Types III and IV primarily rely on PUFA‐S, with Type III lacking the canonical Δ9 desaturase and Type IV missing most desaturase and elongase enzymes. Notably, the Δ9 desaturase and ATP‐citrate lyase ( ACLY ) are exclusive to Types I and II, while β‐carotene hydroxylase ( CrtZ ) is absent in these types. ACLY absence suggests alternative acetyl‐CoA supply pathways in Types III and IV, whereas CrtZ absence implies either a lack of specific xanthophylls or alternative biosynthetic pathways in Types I and II. Synteny analysis revealed conserved genomic organisation of PUFA biosynthetic genes, indicating a shared evolutionary trajectory. This study provides insights into the genetic diversity underlying PUFA biosynthesis in thraustochytrids, while proposing putative evolutionary pathways for the four lineages.

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

Towards effective recovery of humate as green fertilizer from landfill leachate concentrate by electro-neutral nanofiltration membrane - Wenyuan Ye; Mingqiu Hong; Xuan Huang; Tianci Chen; Ailiang Gu; Xiaocheng Lin; Xuewei Li; Xiangrong Chen; Dong Han Seo; Shuaifei Zhao; Xueming Chen; Bart Van der Bruggen; et al. (Science of The Total Environment, 2023)

Promotion of the catalytic polymerization of hydroquinone towards humic-like substances by graphitic carbon nitride - M.M.M. Ahmed; Yu-Ting Liu; S. Venkatesan; Min Chien Wu; Howida M. Nail; Der-Lii M. Tzou; Ming-Chang Lin; Kai-Yue Chen; Yu-min Tzou (Journal of Environmental Chemical Engineering, 2023)

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Association between exposure to road traffic noise and hearing impairment: a case-control study - Tang-Chuan Wang; Ta-Yuan Chang; Richard S. Tyler; Bing-Fang Hwang; Yi-Hung Chen; Che-Ming Wu; Chiu-Shong Liu; Kuang-Chao Chen; Chia-Der Lin; Ming-Hsui Tsai (Journal of Environmental Health Science and Engineering, 2021)

Computed Tomography Super-Resolution Using a Generative Adversarial Network in Bronchoscopy: A Clinical Feasibility Study - Heng-sheng Chao; Tsu-Hui Shiao; Chung-Wei Chou; Fang-Chi Lin; Yu-Te Wu; Der-Ming Liou (Journal of Medical and Biological Engineering, 2021)

Two new diprenylated flavanones from Derris laxiflora Benth - Hui-Chi Huang; Shih-Chang Chien; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Hsi-Lin Chiu; Yueh-Hsiung Kuo (Natural Product Research, 2020)

A stochastic multi-objective optimization decision model for energy facility allocation: a case of liquefied petroleum gas station - Ming-Der Yang; Yi-Ping Chen; Chien-Tsung Wang; Ming-Jay Deng; Yu-Hao Lin; Ho-Wen Chen (Clean Technologies and Environmental Policy, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Secondary metabolites from the fermented rice of the fungus Monascus purpureus and their bioactivities - Ho-Cheng Wu; Ming-Jen Cheng; Ming-Der Wu; Jih-Jung Chen; Yen-Lin Chen; Hsun-Shuo Chang; Kai-Ping Chen (Natural Product Research, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

A Clinical and Kinematical Evaluation of Trajectory Planning Software for Posterior Atlantoaxial Transarticular Screw Fixation Surgery - Andy Chien; Yao-Hung Wang; Dar-Ming Lai; Ying-Sian Chen; Wen-Kai Chou; Been-Der Yang; Jaw-Lin Wang (Journal of Medical and Biological Engineering, 2016)

Multiobjective Optimal Design of Sewerage Rehabilitation by Using the Nondominated Sorting Genetic Algorithm-II - Yu-Hao Lin; Yi-Ping Chen; Ming-Der Yang; Tung-Ching Su (Water Resources Management, 2016)

Influences of environmental and spatial factors on genetic and epigenetic variations in Rhododendron oldhamii (Ericaceae) - Chun-Lin Huang; Jui-Hung Chen; Ming-Hsuan Tsang; Jeng-Der Chung; Chung-Te Chang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

Monascusazaphilones A–C, three new azaphilone analogues isolated from the fungus Monascus purpureus BCRC 38108 - Ming-Der Wu; Ming-Jen Cheng; Yi-Jen Yech; Yen-Lin Chen; Kai-Ping Chen; Ping-Hsun Yang; Ih-Sheng Chen; Gwo-Fang Yuan (Natural Product Research, 2013)

Global transcriptome analysis and identification of a CONSTANS-like gene family in the orchid Erycina pusilla - Ming-Lun Chou; Ming-Che Shih; Ming-Tsair Chan; Shih-Yi Liao; Chen-Tran Hsu; Yao-Ting Haung; Jeremy J. W. Chen; Der-Chih Liao; Fu-Hui Wu; Choun-Sea Lin (Planta, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Role of interleukin 1 beta in esophageal squamous cell carcinoma - Miao-Fen Chen; Ming-Shian Lu; Ping-Tsung Chen; Wen-Cheng Chen; Paul-Yang Lin; Kuan-Der Lee (Journal of Molecular Medicine, 2012)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

A Preliminary Assessment of Polycyclic Aromatic Hydrocarbon Distribution in the Kenting Coral Reef Waters of Southern Taiwan - Jing-O. Cheng; Ying-Ming Cheng; Te-Hao Chen; Ping-Chieh Hsieh; Meng-Der Fang; Chon-Lin Lee; Fung-Chi Ko (Archives of Environmental Contamination and Toxicology, 2010)

The predictive role of E2-EPF ubiquitin carrier protein in esophageal squamous cell carcinoma - Miao-Fen Chen; Kuan-Der Lee; Ming-Shian Lu; Chih-Cheng Chen; Ming-Ju Hsieh; Yun-Hen Liu; Paul-Yang Lin; Wen-Cheng Chen (Journal of Molecular Medicine, 2009)

The Effects of Calcium Channel Blocker Benidipine and Calmodulin Antagonist W7 on GDP-Binding Capacity of Brown Adipose Tissue in Mice - Yuh-Min Song; Pi-Yao Lin; Ming-Der Chen (Biological Trace Element Research, 2009)

Aliphatic and polycyclic aromatic hydrocarbons in sediments of Kaohsiung Harbour and adjacent coast, Taiwan - Chon-Lin Lee; Ming-Tsuen Hsieh; Meng-Der Fang (Environmental Monitoring and Assessment, 2005)

Gene cloning and characterization of a soybean (Glycine max L.) LEA protein, GmPM16 - Ming-der Shih; Shu-chin Lin; Jaw-shu Hsieh; Chi-hua Tsou; Teh-yuan Chow; Tsai-piao Lin; Yue-ie C. Hsing (Plant Molecular Biology, 2004)

Characterization of stress-responsive genes, hrcA-grpE-dnaK-dnaJ , from phytopathogenic Xanthomonas campestris - Shu-Fen Weng; Pan-Ming Tai; Cheng-Hwa Yang; Cheng-Der Wu; Wan-Ju Tsai; Juey-Wen Lin; Yi-Hsiung Tseng (Archives of Microbiology, 2001)

Zinc coadministration attenuates melatonin’s effect on nitric oxide production in mice - Ming-Der Chen; Pi-Yao Lin; Wayne Huey-Herng Sheu (Biological Trace Element Research, 1999)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)

Zinc supplementation on serum levels and hepatic conversion of thyroid hormones in obese (ob/ob) mice - Ming-Der Chen; Pi-Yao Lin; Wen-Han Lin (Biological Trace Element Research, 1998)

Zinc status in plasma of obese individuals during glucose administration - Ming-Der Chen; Pi-Yao Lin; Wayne H. -H. Sheu (Biological Trace Element Research, 1997)

Zinc attenuation of GDP binding to brown adipocytes mitochondria in genetically obese (ob/ob) mice - Ming-Der Chen; Pi-Yao Lin; Piin-Sheng Chen; Vie Cheng; Wen-Han Lin (Biological Trace Element Research, 1997)

Zinc supplementation aggravates body fat accumulation in genetically obese mice and dietary-obese mice - Ming-Der Chen; Pi-Yao Lin; Vie Cheng; Wen-Han Lin (Biological Trace Element Research, 1996)

Dietary copper supplementation increases the catecholamine levels in genetically obese (ob/ob) mice - Wen-Han Lin; Ming-Der Chen; Chih-Chien Wang; Pi-Yao Lin (Biological Trace Element Research, 1995)

Selected metals status in patients with noninsulin-dependent diabetes mellitus - Ming-Der Chen; Pi-Yao Lin; Chung-Tide Tsou; Jyh-Jain Wang; Wen-Han Lin (Biological Trace Element Research, 1995)